The Language of Johannes Brahms's Theme and Variation : A Study of His Chamber Works for Strings - Pepple, Joanna (East Carolina University, 2012)
The variation movements of Johannes Brahms portray a continuous development of his musical discourse. Regarding variation form, he advocated for formal unity and the important role of the bass throughout his letters. In his music, he invented a language of theme and variation capable of creating new structures through old forms. The present analysis studies Brahms's approach to theme and variation through four representative movements from his chamber works for strings: Op. 18/ii, Op. 36/iii, Op. 67/iv, and Op. 111/ii. Comparing these movements reveals a continuous development of his musical rhetoric in the variation genre. By challenging the historic aesthetics of variation technique through a progressive release of structure, Brahms establishes a discursive, goal-directed language within a recurring framework. He thus asserts his individual voice within a traditional form, contributing to the genre of theme and variation with an ongoing, teleological dialogue.
Keywords: Music; History; Performing arts; 19th century music; Chamber music; Nineteenth century music; Recursive; Romantic music; Theme and variation; Brahms, Johannes, 1833-1897--Analysis, appreciation